2023
DOI: 10.1021/acs.jafc.3c04056
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Ratiometric Fluorescent Probe with Zero Cross-Talk for the Detection of SO2 Derivatives in Foods and Live Cells

Huan Peng,
Suna Kong,
Xia Deng
et al.

Abstract: Sulfur dioxide (SO2) derivatives are extensively utilized as both a preservative for foods and an active gaseous signal molecule in various physiological and pathological processes, but their excessive intake would bring harmful effects on human health; so, the determination of SO2 derivatives is of great importance. Herein, we developed a ratiometric fluorescent probe named 2-(2′-hydroxyphenyl)­benzothiazole-3-ethyl-1,1,2-trimethyl-1H-benzo­[e]­indolium (HBT-EMBI) by introducing a hemicyanine unit of EMBI to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…The results suggest that the addition reaction of HSO 3 − /SO 3 2− disrupted the conjugation and the intramolecular charge transfer (ICT) process between diethylaminocoumarin and benzothiazolium salt moieties. 20,21,39 Additionally, a well-established linear relationship ( R 2 = 0.9931) between the fluorescence intensity ratio at 500 nm to that at 690 nm and the concentration of HSO 3 − /SO 3 2− was observed within the range of 0 to 60 μM (Fig. 1E).…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…The results suggest that the addition reaction of HSO 3 − /SO 3 2− disrupted the conjugation and the intramolecular charge transfer (ICT) process between diethylaminocoumarin and benzothiazolium salt moieties. 20,21,39 Additionally, a well-established linear relationship ( R 2 = 0.9931) between the fluorescence intensity ratio at 500 nm to that at 690 nm and the concentration of HSO 3 − /SO 3 2− was observed within the range of 0 to 60 μM (Fig. 1E).…”
Section: Resultsmentioning
confidence: 66%
“…20 The detection limit of CMBT for SO 2 is calculated to be 0.17 μM. 39 These results indicated that the probe CMBT has a longer emission wavelength and excellent sensitivity to SO 2 compared to the reported literature. 8,12,13,15,18…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations